Modulating Nrf2 to control lipid peroxidation and ferroptosis: implications for cancer management - Tunc, Ramazan; Ates, Ilker; Yılmaz, Beyza; Medoro, Alessandro; Davinelli, Sergio; Suzen, Sibel; Saso, Luciano (Frontiers in Oncology, 2025)
Nuclear factor erythroid 2–related factor 2 (Nrf2) is a key transcription factor that regulates the expression of genes involved in cellular protection against oxidative stress and the maintenance of redox homeostasis. In addition to modulating reactive oxygen species (ROS), Nrf2 influences lipid peroxidation (LP) and ferroptosis, an iron-dependent form of regulated cell death driven by lipid peroxide accumulation. Dysregulation of Nrf2 signaling has been implicated in the pathogenesis and progression of several malignancies, where it affects tumor cell survival, chemoresistance, and metabolic reprogramming. This review summarizes current knowledge on the complex relationship between Nrf2 activity, LP dynamics, and ferroptotic mechanisms in cancer biology. It also highlights how Nrf2-dependent transcriptional programs not only regulate antioxidant responses but also contribute to cellular detoxification, metabolism, autophagy, and proteostasis, processes closely linked to tumorigenesis and cancer cell adaptability. Given that Nrf2 may have a dual role in cancer, either promoting cytoprotection or supporting tumor progression and chemoresistance, we discuss emerging strategies to selectively modulate Nrf2 and ferroptosis-related pathways to increase cancer cell sensitivity to oxidative damage and reduce resistance.